Pengaruh Aromaterapi Bergamot (Citrus Bergamia) Terhadap Depresi Post Partum - Sujawaty, Sri; Olii, Nancy; Yulianingsih, Endah; Podungge, Yusni; Rasyid, Puspita Sukmawaty (POLTEKKES KEMENKES MANADO, 2024)
Background : Depression postpartum is a mental health disorder that arises after giving birth. Postpartum Depression after giving birth can be more severe and last longer than